Evaluation of Effective Microorganisms on home scale organic waste composting - Fan, Yee Van; Lee, Chew Tin; Klemeš, Jiří Jaromír; Chua, Lee Suan; Sarmidi, Mohamad Roji; Leow, Chee Woh (Journal of environmental management, 2018)
Home composting can be an effective way to reduce the volume of municipal solid waste. The aim of this study is to evaluate the effect of Effective Microorganism™ (EM) for the home scale co-composting of food waste, rice bran and dried leaves. A general consensus is lacking regarding the efficiency of inoculation composting. Home scale composting was carried out with and without EM (control) to identify the roles of EM. The composting parameters for both trials showed a similar trend of changes during the decomposition. As assayed by Fourier Transform Infrared Spectroscopy (FTIR), the functional group of humic acid was initially dominated by aliphatic structure but was dominated by the aromatic in the final compost. The EM compost has a sharper peak of aromatic CC bond presenting a better degree of humification. Compost with EM achieved a slightly higher temperature at the early stage, with foul odour suppressed, enhanced humification process and a greater fat reduction (73%). No significant difference was found for the final composts inoculated with and without EM. The properties included pH (∼7), electric conductivity (∼2), carbon-to-nitrogen ratio (C: N < 14), colour (dark brown), odour (earthy smell), germination index (>100%), humic acid content (4.5-4.8%) and pathogen content (no Salmonella, <1000 Most Probable Number/g E. coli). All samples were well matured within 2 months. The potassium and phosphate contents in both cases were similar however the EM compost has a higher nitrogen content (+1.5%). The overall results suggested the positive effect provided by EM notably in odour control and humification.
Keywords: kompostování; huminové látky; Humic Substances; Escherichia coli; Soil; Solid Waste; tuhý odpad; půda; Composting